Transportation geotechnics : proceedings of the symposium held at the Nottingham Trent University School of Property and Construction on 11 September 2003 - Frost, M. W.; Nottingham Trent University. School of Property and Construction; Institution of Civil Engineers (Great Britain). East Midlands Geotechnical Group (London : Thomas Telford, 2003)
08